2012
DOI: 10.1177/0309364611431290
|View full text |Cite
|
Sign up to set email alerts
|

Amputee socks

Abstract: Background: The term 'sock ply' may be a source of confusion in prosthetics practice because there may not be a consistent relationship between sock ply and sock thickness. Objectives: The purpose of this study was to characterize how sock ply related to sock thickness for different sock materials commonly used in limb prosthetics. We also evaluated how sock thickness changed under loading conditions experienced while wearing a lower limb prosthesis compared with unstressed conditions. Study Design: Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 3 publications
3
30
3
Order By: Relevance
“…The issue is relevant for people with trans-tibial amputation because socket fit is so sensitive to small volume changes. A study on 10 subjects with trans-tibial limb loss showed that an experienced practitioner, using static fitting procedures, identified sockets oversized by just 0.25 mm mean radial thickness (approximately half the thickness of a new 3-ply Soft Sock (Knit-Rite) while worn on a residual limb during walking [12]) as needing sock addition or other modification [13]. If increasing bladder liquid volume reduces residual limb fluid volume then more bladder liquid may need to be added, either manually or automatically, to compensate.…”
Section: Introductionmentioning
confidence: 99%
“…The issue is relevant for people with trans-tibial amputation because socket fit is so sensitive to small volume changes. A study on 10 subjects with trans-tibial limb loss showed that an experienced practitioner, using static fitting procedures, identified sockets oversized by just 0.25 mm mean radial thickness (approximately half the thickness of a new 3-ply Soft Sock (Knit-Rite) while worn on a residual limb during walking [12]) as needing sock addition or other modification [13]. If increasing bladder liquid volume reduces residual limb fluid volume then more bladder liquid may need to be added, either manually or automatically, to compensate.…”
Section: Introductionmentioning
confidence: 99%
“…Since relationships between ply and thickness vary by sock model and because sock thickness changes over time [12,13,56] , use of a sock thickness caliper may facilitate measurement.…”
Section: Discussionmentioning
confidence: 99%
“…A custom tabletop instrument that applied controlled pressures during measurement was used [12] . Thickness was recorded under four different pressure conditions to reflect the following clinical activities: donned (6.3kPa); donned-conditioned (subject to compressive loading cycles before testing) (6.3kPa); equal weight-bearing (50.6kPa); and stance phase weight-bearing (101.2kPa) [13] .…”
Section: Methodsmentioning
confidence: 99%
“…If the fit was deemed acceptable for regular clinical use, sock thickness was measured using a custom instrument [10]. If sock thickness was less than 1.8mm (approximately the thickness of a new 5-ply sock under weight-bearing) then the participant was continued in the study, and a new socket and insert were created.…”
Section: Methodsmentioning
confidence: 99%